Low Levels Matter: Clinical Relevance of Low Pru p 3 sIgE in Patients With Peach Allergy - Balsells-Vives, Sara; San Bartolomé, Clara; Casas-Saucedo, Rocío; Ruano-Zaragoza, María; Rius, Josefina; Torradeflot, Maria; Bartra, Joan; Munoz-Cano, Rosa; Pascal, Mariona (Frontiers in Allergy, 2022)
Many clinical lab settings still use 0.35 KUA/L as the cut-off for serum specific-IgE (sIgE) immunoassays, while the detection limit is 0.1 KUA/L. The clinical relevance of -low-level sIgE (0.1–0.35 KUA/L) remains controversial. Pru p 3 sIgE is considered to be the main routine tool for assessing lipid transfer protein (LTP) sensitization. We aimed to evaluate the clinical relevance of Pru p 3 sIgE low levels in a population diagnosed with LTP allergy. Adults diagnosed with LTP allergy and Pru p 3 sIgE ≥ 0.1 KUA/L between 2012 and 2019 were included. Clinical data were reviewed. nPru p 3 basophil activation test (BAT) was performed and basophil reactivity (BR) and sensitivity (BS) correlated with the peach allergy symptoms. Pru p 3 sIgE from 496 subjects was recorded, 114 (23.0%) between 0.1 and 0.34 KUA/L (grLOW), the rest ≥ 0.35 KUA/L (grB). A total of 44.7% in grLOW and 59.9% in grB were allergic. Urticaria was more frequent in grLOW. In grLOW, Pru p 3 sIgE was higher in patients with local compared with systemic symptoms. In grB, Pru p 3 sIgE was higher in allergic patients. Pru p 3/Total IgE ratios were higher in allergic vs. tolerant in both groups. In BAT, BR was similar in both groups. In grLOW, it was higher on allergic compared with tolerant (p = 0.0286), and on those having systemic vs. local symptoms (p = 0.0286). BS showed no significant difference between groups. Patients with low levels represent a non-negligible fraction and around 45% are peach allergic. BAT showed functional sIgE in them. Pru p 3 sensitizations should be carefully evaluated even when sIgE levels are low.